Evaluation of functionality and disability of older elderly outpatients using the WHODAS 2.0 - Bruna Veiga; Rita Aparecida Bernardi Pereira; Adriane Miró Vianna Benke Pereira; Renato Nickel (Revista Brasileira de Geriatria e Gerontologia, 2016)
Abstract Objectives: To analyze the level of functionality and disability of older elderly persons receiving care at a university hospital in Curitiba, Paraná, and identify functional differences between men and women. Method: A descriptive, cross-sectional study with a quantitative approach, based on a convenience sample of elderly persons receiving outpatient care, was undertaken. The Brazilian version of the World Health Organization Disability Assessment Schedule (WHODAS 2.0). Results: A total of 28 people with a mean age of 86.21 (±4.17) were evaluated. Of these 50.0 % were male, 46.4 % were widowed, and 57.1 % performed the evaluated activities independently. There were no significant differences between genders in terms of age (p≤0.635) or years of study (p≤0.329), although women showed a higher level of disability than men in general (p≤0.16). Conclusion: The WHODAS 2.0 proved to be a sensitive tool for the analysis and comparison of the level of functionality of the older elderly. However, it is important to develop prospective studies, with non-convenience samples, for a better reflection on the disability and functionality of older elderly persons.